Comunicar no instagram em tempos de pandemia: um estudo de caso do Sesc na Região do Norte - RODRIGUES, Samara Sarmanho (Universidade Federal do Pará, 2024)
The covid-19 pandemic affected people and organizations on a global scale and social isolation, imposed as a safety measure, had a major impact on the world economy. From this, society as a whole needed to adapt and organizations needed to take their communication to the digital environment in order to maintain interaction with their audience and minimize the damage caused by the pandemic. In this way, Social Media, with strong growth during the pandemic period, were essential tools in this process, as they allowed the relationship between the company and the public, seeking to reduce the distance caused by this atypical situation. The problematization of this study concerns how the Social Service of Commerce (Sesc) in the North Region used Instagram as a tool to disseminate its programs in the area of culture and how its communication strategies were changed with the advent of the pandemic, since activities ceased to be face-to-face and began to take place in the digital environment. In this sense, the present master's research seeks to analyze how the covid-19 pandemic modified Sesc's communication strategies on the social media Instagram during the years 2020 and 2021. This study is characterized as mixed methods research (quantitative and qualitative) of the multiple case study type, as it analyzed the seven Sesc in the North Region. First, through exploratory research, publications in the Instagram feed were analyzed in general, and also those related to the area of culture, obtaining data for carrying out the quantitative analysis, as well as for the qualitative analysis. The qualitative character of the research took place through interviews with a semi-structured script with the communication coordinators and their subsequent content analysis. The result found was the intensification of the use of social media as a general communication strategy with the public, in addition to these media serving as a tool for publicizing the institution's various activities and programs. The highlight was the social media Instagram, which was the main social media used and the one that brought the most results for the regionals during the period studied, including the dissemination of activities and programs in the area of culture at Sesc.